Decoding Religious Contents of Grade 5th Textbooks of Single National Curriculum (SNC) in Pakistan - Tayyab , Muhammad; Umer , Saima; Sajid, Akbar (Pakistan Journal of Humanities and Social Sciences, 2022)
Textbooks’ discourses are significant means to disseminate desired ideology to the target readers and make them behave in a certain manner. Discursive strategies employed in this regard play a vital role in making certain ideologies common sense. The present study critically analyses the religious contents of primary English and Urdu textbooks to lay bare implicit and explicit ideologies at work through the Critical Discourse Analysis technique. For this purpose, the data has been collected from the textbooks published during 2021-2022. The selected books are based on Single National Curriculum (SNC). Moreover, the study employs Fairclough (2003, 2013) model of Critical Discourse Analysis (CDA) and Critical Social Analysis (CSA) as a tool of analysis. The relevant data from the mentioned textbooks have been selected and analyzed. The study highlights that fifty percent (50%) of the contents from the selected books carry religious ideology in one way or the other. The language used in the Urdu textbook for the dissemination of religious ideology is more persuasive. Additionally, the propagation of middle-class morality is more obvious in the Urdu textbooks. The study concludes that though the selected books are based on Single National Curriculum, their target readership is more from the middle class as compared to the elite class because the middle class is more in number. Hence, it implies that textbooks at the primary level play a significant role in shaping the mindset of young learners in the desired manner.